New records of rove-beetles (Insecta, Coleoptera, Staphylinidae) for Azores Islands (Portugal) - Borges, Paulo A. V. (2022)
The data we present consist of an updated checklist of the Azorean Staphylinidae (Insecta, Coleoptera), by compiling new identified records of three recent published studies about Azorean arthropods. In general, the records were obtained from different standardised sampling campaigns and from non-standardised observations. The presented records were collected between July 1999 and September 2020, in five islands of the Azores Archipelago: Flores, Graciosa, Terceira, São Miguel and Santa Maria. The samples include records collected in several habitat types, such as native, mixed and exotic forests, pasturelands and agricultural areas (maize fields, orchards, citrus areas and vineyards). This inventory represents the most updated checklist and knowledge about Staphylinidae in Azores and new information includes one new exotic rove-beetle for the Azores (Thecturota tenuissima Casey, 1893) and seven new islands records.